Analisis Strategi Pemasaran Produk Tabungan Smart iB Pada Bank Sumut Kantor Cabang Pembantu Syariah Marelan Raya - Nurhayati Nurhayati; Atika Atika (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Islamic banking which continues to grow rapidly at this time has resulted in competition in the banking industry, both between Islamic banking and conventional banking or fellow Islamic banks in obtaining their respective income. Every bank strives to create product innovations to be the best in order to increase the collection of funds originating from the public in the form of savings. The method used in this research is a qualitative method. Qualitative method is research that explains data in the form of written or spoken words from someone whose behavior is observed. PT. Bank Sumut Marelan Raya Sharia Sub-Branch Office is one of the banks that is competing to earn its income by making a Smart iB savings product which is one of the superior savings products at the bank and uses the Mudharabah Mutlaqah principle where the mudharabah contract gives full freedom to mudharib in managing capital provided by shahibul mal. Mudharib can use this capital for investment or business. This Smart iB Savings uses a ratio or profit sharing that will later be mutually agreed upon.